COMMUNICATION NETWORK MODEL FOR THE FAST REACTION TEAM PROGRAM (TRC) “SARIBATTANG” CHILDREN IN MAKASSAR CITY - Tuti Bahfiarti; Arianto Arianto; Burhanuddin Burhanuddin (Badan Penelitian dan Pengembangan Daerah Kota Makassar, 2017)
The communication network helps provide the direction and policies of the Quick Response Team (TRC) Program